The promising variety of alfalfa (Medicago polymorpha) “Golubka” - S. A. Ignatiev; T. V. Gryazeva; G. V. Metlina; N. G. Ignatieva (Зерновое хозяйство России, 2018)
The promising variety of alfalfa ( Medicago polymorpha) “Golubka” The article considers the study of a new alfalfa variety “Golubka” and gives its morpho-biological description. Today, the variety is the main source for the production of saturated feed energy, the carrier of certain economically valuable traits. For each region it’s necessary to have the varieties that are able to realize soil-climatic conditions of the area and possess resistance to different stress factors. Taking into consideration this fact and the variability of soil-climatic conditions of the Rostov region, the work is directed on developing of the varieties, capable to use bioclimatic resources of the region more efficiently. The main direction of selection fulfilled by the laboratory of perennial grasses is to develop the varieties for hay and pasture use with good productivity of forage mass, seeds, resistance to principle diseases and unfavourable environmental factors. The study was carried out by the method of developing of hybrid populations on the basis of biotypes, obtained by multiple selections due to forage and seed productivity. The alfalfa variety “Golubka” produced 31.0 t/ha of green chop, 9.3 t/ha of dry matter and 0.22 t/ha of seed productivity. The alfalfa variety “Golubka” exceeded the standard variety “Rostovskaya 90” in green mass productivity on 7.6%, in dry matter yield on 6.9%, in seed productivity on 11%. The green mass contains 21.0-21.8% of raw protein and 30-32% of fiber. The new alfalfa variety “Golubka” has a greater yield of fodder units (on 7.6%) and raw protein (on 9.0%) per 1 hectare. One kg of dry matter of the variety “Golubka” contains a larger amount of changeable energy (10.4 MJ/kg) and digestible protein (153 g/kg), its fodder unit is better supplied with digestible protein (187 g/f.u.).